Advancing Law Enforcement Efficiency Through Integrated Technological Innovation Systems - Ngatmo Ngatmo (Universitas Negeri Semarang, 2025)
Technological innovation has transformed modern policing by enhancing operational efficiency, investigative accuracy, and public safety. This study examines the integration of digital tools—including surveillance systems, artificial intelligence, mobile reporting platforms, cyber forensics, and geographic information systems—into law-enforcement practices. Using a mixed-methods approach, the research analyzes five-year operational datasets from metropolitan police agencies, 54 interviews with officers and IT specialists, and documentation of technology implementation policies. The results show that the adoption of integrated technological systems leads to a 28% improvement in response times, a 34% increase in investigative clearance rates, and enhanced predictive capabilities in crime pattern analysis. Qualitative findings highlight that officers perceive technology as beneficial for situational awareness but express concerns regarding privacy, data security, and overreliance on automated systems. The study concludes that responsible and strategic use of technology strengthens police effectiveness while requiring robust ethical governance and transparent public communication. This research contributes to public safety science by offering a comprehensive framework for evaluating technological integration and proposing guidelines for sustainable and accountable digital transformation in policing.